English learning websites and digital resources from the perspective of Chinese university EFL practitioners. Issue 2 (20th May 2014) - Shen, Huizhong; Yuan, Yifeng; Ewing, Robyn
Abstract: English language learning (ELL) websites and digital resources have been recognized as an important source of linguistic and cultural knowledge for English as a foreign language (EFL) learners to explore. The up-to-date information carried by authentic materials is invaluable for learners to develop an understanding of the target language/culture. However, there appears to be a gap between what the designer intends and what the user wants. This paper investigates Chinese university EFL teachers' perceptions of online English language websites and resources. The study focuses on a number of components of major language areas and skills in ELL websites, website materials, language users' preferences, and website usability. A total of 1519 English academics from 139 universities across China completed the online survey, and 164 of them voluntarily participated in focus group interviews anonymously. The empirical evidence of this study has highlighted that a pedagogically-oriented ELL website, targeting audiences with a variety of language proficiencies, was much liked by the Chinese EFL teachers. A preference was observed to see more current authentic language, examination-oriented English learning materials and tasks, and Eastern/non-Anglophone topics in the websites. In addition, it is found that website usability is another key factor that would impact ELL website popularity. A well-designed ELL website can effectively assist Chinese EFL learners to enhance their language competence and achieve optimal learning outcomes. This study provides a context-specific empirical base for innovative web-based EFL learning and teaching as well as website design and materials development in China. The proposed key features of a preferred ELL website may help better inform website designers, content writers and evaluators in their ELL website design/evaluation.